Reversibility of retinal ischemia due to central retinal artery occlusion by hyperbaric oxygen - Hadanny, Amir (Clin Ophthalmol, 2016)
PURPOSE: Ischemic retinal damage can be reversed by hyperbaric oxygen therapy (HBOT) as long as irreversible infarction damage has not developed. However, the time window till irreversible damage develops is still unknown. The study aim was to evaluate the effect of HBOT and determine possible markers for irreversible retinal damage. MATERIALS AND METHODS: Retrospective analysis of 225 patients treated with HBOT for central retinal artery occlusion (CRAO) in 1999–2015. One hundred and twenty-eight patients fulfilled inclusion/exclusion criteria: age >18 years, symptoms <20 hours, and best-corrected visual acuity (BCVA) <0.5 logMAR. RESULTS: Time delay from symptoms to treatment was 7.8±3.8 hours. The BCVA was significantly improved after HBOT, from 2.14±0.50 to 1.61±0.78 (P<0.0001). The proportion of patients with clinically meaningful visual improvement was significantly higher in patients without cherry-red spot (CRS) compared to patients with CRS at presentation (86.0% vs 57.6%, P<0.0001). The percentage of patients with final BCVA better than 1.0 was also significantly higher in patients without CRS vs patients with CRS at presentation (61.0% vs 7.1%, P<0.0001). There was no correlation between CRS and the time from symptoms. HBOT was found to be safe, and only 5.5% of patients had minor, reversible, adverse events. CONCLUSION: HBOT is an effective treatment for non-arteritic CRAO as long as CRS has not formed. The fundus findings, rather than the time delay, should be used as a marker for irreversible damage.